Resilient Social Work Practice: From the Experiences of Filipino Social Workers - Laro, Amelyn (Indonesian Social Work Consortium (ISWC), 2023)
'Resilience' refers to a person's capacity to handle difficulties, demands and pressure without experiencing negative effects. The concept of resilience draws from and reinforces a strengths perspective. The term refers to the belief that we have personal wisdom and capacity to persevere and grow from experience. Adopting a resilience mindset helps us to tap into these capacities and to flourish, even in the face of challenge. The pressures and demands of social work practice requires social workers to remain steadfast and strong despite all the personal and professional challenges. Since our country experiences many challenges like natural and manmade disaster and the COVID 19. There are evidence that social workers had experience mental and emotional fatigue. A study which aims to describe Resilient social work practice and actual experiences of Filipino Social Workers both personally and professionally amidst challenges and pandemic is needed to shed some light on how Filipino Social Workers deals with all these difficulties. Specifically, the study answers the following questions: 1. What is their perspective of resilient social work? 2.What are examples of resilience as practice by social workers on a personal and professional level? 3.How do social workers build resilience in professional practice? 4. In what ways (what aspect of their personal and professional level) did the participants practice Resiliency? Through online platform social workers in Davao Region from different social work settings participated in the study descriptive-qualitative research and concluded that social workers utilized various resiliency tools both personal and professional in their practice in dealing with clients in various organizations.